RESPONSE OF LAKE BAIKAL ECOSYSTEM TO CLIMATE FORCING AND PCO2 CHANGE OVER THE LAST GLACIAL/INTERGLACIAL TRANSITION - Prokopenko A.A.; Williams D.F.; Karabanov E.B.; Khursevich G.K. (My University, 1999)
The δ13C record of total organic carbon in the Lake Baikal core BDP-93-2 over the last glacial/interglacial transition shows remarkable correlation with atmospheric CO2 fluctuations and the negative isotopic shift of 3.5–4‰ in response to the global increase in paleo-pCO2 level. With rapid evolution of the Lake Baikal carbon cycle from full glacial to full interglacial modes, however, the pCO2 signal in the Baikal δ13C sedimentary organic matter is inundated by the basin-wide productivity signal, in the Holocene. The Baikal diatom abundance record, as a paleotemperature proxy, lags behind the GISP2 ice core δ18O temperature proxy record by ca. 1 ka, possibly reflecting the response time of the Baikal ecosystem to major climatic transitions. There is no lag associated with the pronounced Younger Dryas cooling, however, suggesting a different forcing mechanism, with a short response time, for this abrupt climatic event in continental interior Asia. The phase difference observed between the diatom abundance and δ13C proxies in Lake Baikal core BDP-93-2 suggests their independent responses to different forcing mechanisms, further justifying their importance for paleoclimate reconstructions from Lake Baikal records.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен